Construction of a new clinical staging system for colorectal cancer based on the lymph node ratio: A validation study - Yang, Yan; Wang, Yawei; Wang, Zhengbing (Frontiers in Surgery, 2022)
Aim: To construct a new staging system of colorectal cancer (CRC) based on lymph node ratio (LNR) as a supplement to the American Joint Committee on Cancer (AJCC) tumor-node-metastasis (TNM) staging system for predicting the prognosis of CRC patients with <12 lymph nodes. Methods: The data of 26695 CRC patients with <12 lymph nodes were extracted from Surveillance, Epidemiology, and End Results (SEER) database as the training set. 635 CRC patients were also enrolled from Northern Jiangsu People’s Hospital affiliated to Yangzhou University as an independent validation set. Classification and regression tree analysis was used to obtain the LNR cutoff value. Survival curves were estimated using the Kaplan-Meier method, and the log-rank test was used for comparisons of differences among the survival curves. The monotone decreasing trend of the overall survival (OS) curve in the staging system was expressed by the linear correlation degree R. Results: The 5-year survival rate of patients in the training set based on AJCC staging system from stage I to stage IV were 75.6% (95%CI: 74.4-76.8), 59.8% (95%CI: 58.6-61.0), 42.1% (95%CI: 34.5-49.7), 33.2% (95%CI: 24.6-41.8), 72.0% (95%CI: 69.1-74.9), 48.8% (95%CI: 47.4-50.2), 26.5% (95%CI: 23.0-30.0), and 11.3% (95%CI: 10.3-12.3). The 5-year survival rates of patients in the training set from stage I to IIIC were 80.4%, 72.9%, 59.8%, 48.4%, 32.5% and 15.0% according to TNM + LNR (TNRM) staging system. According to the AJCC staging system, the 5-year survival rates of patients in the validation set from stage I to stage IIIC were 91.3%, 90.8%, 72.6%, 61.3%, 72.4%, 58.1% and 32.8%, respectively. Based on TNRM staging system, the 5-year survival rates of patients in the validation set from stage I to stage IIIC were 99.2%, 90.5%, 81.4%, 78.6%, 60.2%, and 35.8%, respectively. Conclusion: TNRM staging system successfully eliminated “survival paradox” in AJCC staging system, which might be superior to AJCC staging system.